2022
DOI: 10.2147/ott.s364566
|View full text |Cite
|
Sign up to set email alerts
|

FGFR2-ERC1: A Subtype of FGFR2 Oncogenic Fusion Variant in Lung Adenocarcinoma and the Response to Anlotinib

Abstract: Background Fibroblast growth factor receptor (FGFR) fusions in non-small cell lung cancer (NSCLC) are small genomic events. At present, there is no standard treatment strategy for patients with NSCLC carrying an FGFR fusion. Case Presentation We report the case of a 45-year-old female patient who was diagnosed with lung adenocarcinoma and underwent right upper lobectomy and postoperative adjuvant chemotherapy. After 13 months, the patient’s lung lesions progressed. Next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The preclinical results showed that anlotinib can significantly inactivate FGFR1–4, especially FGFR2 [ 39 ]. Lung adenocarcinoma patients with FGFR2 fusion may benefit from anlotinib [ 40 ]. In this study, we confirmed that FGF6 amplification can not only promote the phosphorylation of FGFR, but also promote the phosphorylation of AKT/ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The preclinical results showed that anlotinib can significantly inactivate FGFR1–4, especially FGFR2 [ 39 ]. Lung adenocarcinoma patients with FGFR2 fusion may benefit from anlotinib [ 40 ]. In this study, we confirmed that FGF6 amplification can not only promote the phosphorylation of FGFR, but also promote the phosphorylation of AKT/ERK pathway.…”
Section: Discussionmentioning
confidence: 99%